DIRECT MEDICAL COSTS OF TREATING DIABETIC FOOT ULCERS AMONG ADULT FILIPINOS AT THE PHILIPPINE GENERAL HOSPITAL - Lusica, Patricia Marie; Eugenio, Kyle Patrick; Jimeno, Cecilia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Diabetic foot ulcers account for 16-20% of medicine admissions in the national referral center - the Philippine General Hospital (PGH). This study aimed to determine the direct medical costs of hospitalization for diabetic foot ulcers (DFU) among adult Filipinos. METHODOLOGY A cross-sectional analytic study design was used, with data taken from Filipino adults admitted for DFU from January to September 2019 and 2020. RESULTS There were 437 (308 from 2019, 127 from 2020) included patients, with 59% males, 45.31% from the National Capital Region, and 29.5% had hypertension as comorbidity. The mean age was 56.88 (range: 22-87, SD 11.66). The mean length of hospital stay was 15.5 days (1-102). Seventy percent of the patients underwent surgery. The average cost per patient in 2019 was Php 60,925 (USD 1,177), and Php 82,610 (USD 1,595) in 2020. The highest cost was from medications (antibiotics), followed by diagnostics and then operation fees. For national health insurance (Philhealth) members, coverage is not sufficient for DFU admissions because it only subsidizes a maximum of 50-70% of the total cost among surgical cases. The most common operation done was below-the-knee amputation (45.7% in 2019, 41.6% in 2020), debridement (25.3% in 2019, 13.48% in 2020), and ray amputation (19.5% in 2019, 16.9% in 2020). Most cases were University of Texas Staging System IID (37% in 2019, and 44.6% in 2020). CONCLUSION The cost per DFU patient is financially catastrophic for the minimum wage Filipino because it costs at least 40% of the annual income.